2019
DOI: 10.1590/0037-8682-0197-2018
|View full text |Cite
|
Sign up to set email alerts
|

Different susceptibilities of Aedes aegypti and Aedes albopictus larvae to plant-derived products

Abstract: Introduction: Aedes aegypti and Aedes albopictus are important vectors that transmit arboviruses to human populations. Methods: Natural products were obtained and tested against larvae collected from the field in Fortaleza, capital of Ceará state. Results: The essential oils of Syzygium aromaticum (Ae. aegypti LC 50 = 32.7 ppm and Ae. albopictus LC 50 = 138.1 ppm) and Croton nepetaefolius (Ae. aegypti LC 50 = 81.7 ppm and Ae. albopictus LC 50 = 76.1 ppm) showed the most intense larvicidal activity. Conclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
1
15
0
3
Order By: Relevance
“…It is worth noting that the LC 50 values reported here were significantly lower than those reported by other studies with L3 Ae. aegypti larvae using natural compounds, such as plant extracts and essential oils (mostly of LC 50 values between 10 and 100 mg L ‐1 20,35,36 ), as well as other PS, as porphyrin derivates (LC 50 = 2.11 mg L −1 in diffuse solar light 37 ), eosin methylene blue (optimal concentrations between 5 and 50 mg L −1 in RGB white LEDs 38 ) and Photogem® (optimal concentrations between 20 and 80 mg L −1 in artificial and natural light 39 ). Moreover, our LC 50 values were also lower or similar in scale to those larvicides currently recommended by WHO, such as diflubenzuron (0.9 mg L −1 to Rockefeller strain 40 ), Spinosad (0.02 mg L −1 to Rockefeller strain 41 ) and Bacillus thuringiensis israelensis ( Bti) (0.06 mg L ‐1 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the LC 50 values reported here were significantly lower than those reported by other studies with L3 Ae. aegypti larvae using natural compounds, such as plant extracts and essential oils (mostly of LC 50 values between 10 and 100 mg L ‐1 20,35,36 ), as well as other PS, as porphyrin derivates (LC 50 = 2.11 mg L −1 in diffuse solar light 37 ), eosin methylene blue (optimal concentrations between 5 and 50 mg L −1 in RGB white LEDs 38 ) and Photogem® (optimal concentrations between 20 and 80 mg L −1 in artificial and natural light 39 ). Moreover, our LC 50 values were also lower or similar in scale to those larvicides currently recommended by WHO, such as diflubenzuron (0.9 mg L −1 to Rockefeller strain 40 ), Spinosad (0.02 mg L −1 to Rockefeller strain 41 ) and Bacillus thuringiensis israelensis ( Bti) (0.06 mg L ‐1 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…The susceptibility of A. aegypti larvae to GEs under laboratory conditions was tested using dipping methods. The larvicidal activity of a compound is usually improved by increasing its concentration and exposure time, as Rodrigues et al [64] reported for plant-derived bioactive products, such as essential oils, ethanol extracts and FAMEs. In the current study, C. echinulata- GEs showed a strong insecticidal activity against A. aegypti larvae with LC50 0.541 mg/L, which could be probably attributed to the presence of GLA in significant concentrations, followed by EPA-GEs, olive oil-GEs, and N. gaditana -GEs, demonstrating LC50 10.24, 12.88 and 16.92 mg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus larvae. Croton nepetaefolius presented the LC 50 of 76.1 µg.mL −1 [24], Allium macrostemon showed LC 50 of 72.86 µg.mL −1 [40], Piper capitarianum had LC 50 of 161.81 µg.mL −1 [41]; and Rosmarinus officinalis had LC 50 of 104.6 µg.mL −1 [42].…”
Section: Larvicidal Activity Of L Grata Essential Oils Against Larvae Of Ae Aegypti and Ae Albopictusmentioning
confidence: 99%
“…Research on the larvicidal activity of essential oils against Ae. albopictus larvae is scarce, given the vector's potential to spread arboviruses [24]. Other studies have identified that the essential oil yield, number of constituents, and relative proportions of secondary metabolites in plants are regulated by biotic and abiotic factors, such as season, area, and sample collection time, showing the relevance of chemical and biochemical studies with plants collected in different regions and at different times of the year [23,25].…”
Section: Introductionmentioning
confidence: 99%